Recurrent anterior shoulder instability: Why do the patients decide on the treatment late? (Annals of Medical Research, 2021)
Aim: Anterior shoulder instability is a condition that frequently occurs in young and active patients and reduces quality of life. In their daily practice, the authors have noticed that patients presenting to their clinic with anterior shoulder instability took longer to decideon treatment compared with reports in the literature. The aim of the present study was to investigate the reasons why patients who experience recurrent anterior shoulder instability delay treatment decisions in Turkey.Materials and Methods: A total of 49 patients, who underwent arthroscopic repairs due to anterior shoulder instability between March 2015 and January 2019, were administered a survey prepared by the authors at regular patient follow-ups.Results: Patients participating in this study experienced an average of 21.78 (range, 2–100) dislocations in the period from the first episode of dislocation to surgery. The mean time from the first dislocation to surgery was 5.5 years (range, 1–266 months). Academic degree, living area, distance from hospital, first dislocation time, first episode to surgery time, dislocation count, operation advicing time after dislocation, patient decision after dislocation, type of surgery were statistically insignificant.Conclusion: Patient responses to the survey questions indicated that delayed decisions for surgery resulted from concerns with absence from work. We believe that patients’ inclination to delay surgery due to their work and financial concerns are understandable considering existing conditions in Turkey. The high number of patients examined daily in our country may be the most important reason for incomplete information of patients.